Preoperative Parameters for Predicting the Loss of Lordosis After Cervical Laminoplasty. Issue 21 (1st November 2020) - Kim, Kwang-Ryeol; Lee, Chang-Kyu; Park, Jeong-Yoon; Kim, In-Soo
Abstract : Study Design: Retrospective study. Objective: The preoperative parameters for predicting the loss of lordosis after cervical laminoplasty were investigated in the present study. Summary of Background Data: Cervical laminoplasty is an effective surgical method to decompress the cervical spinal cord. Maintaining cervical lordosis after laminoplasty is an important factor to ensure the successful surgical treatment. To know the preoperative parameters for predicting loss of lordosis after cervical laminoplasty is important for better outcome after laminoplasty. Methods: In this retrospective study, 106 patients who underwent cervical laminoplasty from 2011 to 2015 were reviewed. The preoperative parameters; T1 slope (TS), Cobb lordotic angle (CLA) and sagittal vertical axis (SVA) at C2–C7, relative cross-sectional area (RCSA), and fatty degeneration of deep extensor muscles (DEMs) were measured. Visual analogue scale (VAS) and modified Japanese Orthopedic Association (mJOA) scores were used for clinical assessment. Correlation analysis was performed between the postoperative CLA change and preoperative parameters. The patients were divided into the decreased- or maintained-lordosis groups based on the difference between postoperative and preoperative CLA. All preoperative parameters were compared between groups. Results: Based on correlation analysis, preoperative TS ( P = 0.001), TS–CLA ( P = 0.046), RCSA at C7–T1 ( P < 0.001), and fatty degeneration of DEMs ( P < 0.001) were correlated with loss of lordosis. Among the 106 patients, 68 showed decreased-lordosis and 38 maintained-lordosis. Preoperative TS ( P = 0.003), SVA ( P = 0.014), TS–CLA ( P = 0.015), and RCSA at C7–T1 ( P = 0.005) were significantly different between groups. In both correlation and comparative analyses, higher TS and TS–CLA and less RCSA at C7–T1 were associated with loss of lordosis. Neck pain VAS ( P < 0.001) and mJOA scores ( P < 0.001) were significantly improved in the maintained-lordosis group. Conclusion: Maintaining cervical lordosis is important for clinical outcomes after laminoplasty. Preoperative higher TS, TS–CLA, and less RCSA at C7–T1 were considered as predictors for loss of lordosis. These characteristics should be considered when choosing the surgical method to help maintain cervical lordosis. Level of Evidence: 3 Abstract : Loss of lordosis after cervical laminoplasty is an important concern and maintaining-lordosis is associated with better outcomes. Preoperative higher T1 slope and less muscle volume of C7–T1 were associated with loss of lordosis after laminoplasty. These characteristics should be considered when choosing the surgical method to help maintaining-lordosis.